Effect of photographs on shopping behavior of consumers - James Ravindran Santhakumar, Meetha Nesam (Kansas State University, 2018)
With increasing global e-commerce scenario, online shopping has become a part of our day-to-day life for products ranging from food to clothing and electronics. With globalization on one hand and tremendous change in the lifestyle of people, on the other hand, eating food outside of the home has also become an inevitable part of life nowadays. This study was designed to understand how photographs and information of the products influence the purchase behavior of consumers, to increase the purchase intent and liking of clothing sold online and food in a restaurant. The objectives of this study were to determine which type of photograph/description would have higher liking and purchase intent by consumers when they are shopping for clothes online and when ordering food in a restaurant. It also aimed to use different types of product descriptions to find any differences in overall liking, product perception, and purchase intent. An online survey was conducted with Indian women (n=600) through Qualtrics software. Data about demographics, overall liking, purchase intent and level of information gained based on the photographs were inquired for different type of photographic presentation of saris and Indian curries in two different sections. ANOVA, Correspondence Analysis (CA), frequency count analysis and descriptive statistics were employed for data analysis using XLSTAT software. In case of online shopping for clothing, especially saris, the results revealed that adding photographs of a model with/without a description to be a better presentation method as it acts as a virtual representation of the seller and is believed to establish trust between the consumers and the sellers. This thereby would lead to significantly higher overall liking, level of being informed and purchase intent. Similarly, in the case of restaurant shopping for food where the effect of photographs on a restaurant menu was studied, adding photographs of the food along with the sides with/without description was found to be a better presentation method. This was in turn related to significantly higher overall liking, level of being informed and purchase intent. Though there are no differences in the type of description added to the picture, adding information about the product was still found to be a critical factor for higher liking and purchase intent in both cases.
Keywords: Photographs; Shopping behavior; Consumers; Sari; Online shopping; Restaurant menu